2020
DOI: 10.1101/2020.07.15.20154906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher Comorbidities and Early Death is Characteristic of Hospitalized African-American Patients with COVID-19

Abstract: Background African-Americans/Blacks have suffered higher morbidity and mortality from COVID-19 than all other racial groups. This study aims to identify the causes of this health disparity, determine prognostic indicators, and assess efficacy of treatment interventions. Method We performed a retrospective cohort study of clinical features and laboratory data of COVID-19 patients admitted over a five-week period at the height of the pandemic in the United States. This study was performed at an urban academic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Six studies initially identified in preprint were subsequently excluded since they had not been peer-reviewed and published by 28 th January 2021; additionally, one study that was initially included based on preprint was subsequently removed since the peer-reviewed version did not meet our study's inclusion criteria. In total, 59 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] were selected for the qualitative synthesis, of which 39[ [23] , [24] , [25] , …”
Section: Resultsmentioning
confidence: 99%
“…Six studies initially identified in preprint were subsequently excluded since they had not been peer-reviewed and published by 28 th January 2021; additionally, one study that was initially included based on preprint was subsequently removed since the peer-reviewed version did not meet our study's inclusion criteria. In total, 59 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] were selected for the qualitative synthesis, of which 39[ [23] , [24] , [25] , …”
Section: Resultsmentioning
confidence: 99%
“…Table S4). In quantitative analysis, 10 studies were excluded as seven [21][22][23][24][25][26][27] only reported Pvalue and three [28][29][30] reported different effect measures.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Consequently, a total of 35 studies with 14,502 patients were included in this systematic review, where 7918 patients were male (54.6%), and hypertension (4940 [34.1%]) as well as diabetes (4540 [31.3%]) were the most reported comorbidities (Appendix Table S4 ). In quantitative analysis, 10 studies were excluded as seven 1824 only reported P-value and three 2527 reported different effect measures.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 1177 articles, of which 636 were deduplicated and 482 were excluded following title and abstracts screening, resulting in the retrieval of 59 records for full-text assessments-among which 13 Table S4). In quantitative analysis, 10 studies were excluded as seven [18][19][20][21][22][23][24] only reported P-value and three [25][26][27] reported different effect measures.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation